Vulneración del Principio de Proporcionalidad en la Sanción por el Delito de Robo con Fuerza en las Cosas Estipulado en el Inciso Segundo del Art. 189 del COIP afecta fundamentalmente los Derechos de los Infractores - Guerrero Jiménez, Brayan David (2018)
The present research work that bears the title '' Infringement of the principle of proportionality in the crime of theft with force in the things stipulated in the second paragraph of art. 189 of the COIP fundamentally affects the rights of the offenders ", establishes that the operators of justice impose very excessive, disproportional sanctions on the people who comment on this crime, without taking into account the amount of the thing stolen, which in many cases does not it exceeds a basic unified salary, thus violating the principle of proportionality, which is typified in article 76 number 6 of our Constitution of the Republic of Ecuador. Within the Organic Comprehensive Criminal Code, referring to the crime of theft with force in things, it creates the need to reform the second paragraph of Article 189 which defines penalties of three to five years of deprivation of liberty, against persons who They commit this crime, considering that in the application of penalties the value of the stolen property must be taken into account and the principle of proportionality applied. Within this thesis the general objective was to carry out a conceptual, legal and doctrinal study of the violation of the principle of proportionality, in the crime of theft with force in the things stipulated in the second paragraph of Article 189 of the Organic Comprehensive Criminal Code fundamentally affects the rights of the offenders, and the specific ones that are: determine 5 that there is no proportionality in the sanction established in the second paragraph of Article 189 of the Comprehensive Organic Code regarding theft with force in things, and show that it is affected the rights of the offender to sanction with the provisions of the second paragraph of Article 189 of the Comprehensive Criminal Code, in the same way to draft a legal reform to the Comprehensive Organic Criminal Code to establish a penalty that is proportional and does not violate the rights of the offender the same as the infraction is related to the penalty. The following hypothesis was proposed. The penalty established in the second paragraph of Article 189 of the Comprehensive Criminal Code are violating the fundamental rights of the offender by applying disproportionate penalties to the offense, for which methods, interview techniques and surveys were applied. All this helped me to formulate the proposal of reform the penalty established in the Organic Comprehensive Penal Code in force respecting the principle of proportionality and in this way does not violate the right that citizens have which is the right to freedom, without the theft of an object less than a salary unified basic must be sanctioned with excessive penalties of up to 5 years, that is why I consider necessary the creation, modification and application of this reform proposal.